Conceptual Framework For The Adoption Of General Takaful Among MSME Owner-Managers In North-west Nigeria: The Role Of MSME Owner-Manager Characteristics - Nurudeen Abdulkadir; Safeza Mohd Sapian; Norhazlina Ibrahim; Syadiyah Abdul Shukor (IIUM Institute of Islamic Banking and Finance (IIiBF), 2024)
Indexed by MyCite